"This Is Not a Parade, It's a Protest March": Intertextuality, Citation, and Political Action on the Streets of Bolivia and Argentina. Issue 2 (4th March 2015) - Lazar, Sian
ABSTRACT Street demonstrations are a common form of political action across Latin America and globally. In this article, I explore some aspects of their symbolic and experiential power, with a focus on ideas of physical and visual intertextuality and their importance in the construction of political agency. I do so through an examination of the symbolic and aesthetic experiential politics of dances, parades, and demonstrations in Bolivia, suggesting that similarities between these practices constitute a kind of citation, which enables each to partake of the symbolic power and resonance of the others. I then investigate the similar political and symbolic work done in Argentine demonstrations by visual (and auditory) intertextuality—but in this case across practices separated by time. I argue that the concept of intertextuality enables an understanding of agency that is not confined to conscious human intentionality and that acknowledges readers as much as actors. [political ritual, street protests, intertextuality, citation, political agency, Bolivia, Argentina, Latin America]